Aberrant cytokeratin expression as a possible prognostic predictor in poorly differentiated colorectal carcinoma. Issue 12 (December 2013) - Yamagishi, Hidetsugu; Imai, Yasuo; Okamura, Takuya; Fukuda, Kazunori; Ono, Yuko; Ban, Shinichi; Inoue, Tohru; Ueda, Yoshihiko
Abstract Background and Aim The cytokeratin (CK)7−/CK20+ immunoprofile is characteristic of colorectal carcinoma (CRC), although CK7+ or CK20− phenotypes are occasionally encountered, particularly in histologically variant CRCs. We analyzed CK7/CK20 profiles in variant CRCs in association with clinicopathologic parameters and prognosis. Methods CK expression in well‐ and moderately differentiated adenocarcinoma (WMDA) (n = 63), poorly differentiated adenocarcinoma (PDA) (n = 91), mucinous adenocarcinoma (MUA) (n = 81), signet‐ring cell carcinoma (SRCC) (n = 15), undifferentiated carcinoma (UDC) (n = 12), and adenosquamous carcinoma (n = 2) was analyzed using immunohistochemistry. Cut‐off scores were set at 1% for CK7 and 25% for CK20 using the receiver operating characteristic curve analysis of PDA. Association between CK20− and better prognosis in PDA was validated in the second cohort (n = 66). Results CK7/CK20 immunoprofiling revealed a predominant CK7−/CK20+ profile in WMDA, MUA, and SRCC, while the majority of UDC was characterized by a CK7−/CK20− profile. The CK7/CK20 profile in PDA was variable. Contingency table analysis revealed that CK expression was not significantly associated with any clinicopathologic parameters in WMDA, PDA, and MUA. However, survival analysis demonstrated that CK20− was significantly associated with better prognosis in PDA. Although CK20− was significantly associated with mismatch repair deficiency in PDA, it was an independent prognostic factor in multivariate analysis. Finally, we confirmed that CK20 status, determined using a 25% cut‐off score, was a significant prognostic parameter in the second PDA cohort. Conclusions CK20 status may be used as a prognostic predictor of PDA.